TAXPAYER COMPLIANCE FACTORS ON MOTOR VEHICLES AT SAMSAT CENTRAL JAKARTA - Putri, Nadia Rida; Masripah, Masripah (Jurnal Akuntansi, Keuangan, Perpajakan dan Tata Kelola Perusahaan, 2025)
Taxes are the most important contribution as a source of funds for the government to finance state needs such as funding national development. This research aims to determine whether there is an influence of taxpayer awareness, service quality and tax sanctions on motor vehicle taxpayer compliance (case study: two-wheeled motorized vehicles at SAMSAT Central Jakarta). This research uses a quantitative method by conducting a survey in the form of a questionnaire to taxpayers on two-wheeled motorized vehicles registered with SAMSAT, Central Jakarta. The sampling technique uses probability sampling with a sample size of 104 respondents. Data was processed and tested using the Partial Least Square method with the SmartPLS 3.0 application. The results of this research indicate that taxpayer awareness and service quality have a significant effect on taxpayer compliance for two-wheeled motorized vehicles at SAMSAT Central Jakarta. Meanwhile, tax sanctions have no influence on taxpayer compliance for two-wheeled motorized vehicles at the Central Jakarta SAMSAT.   Keywords: Taxpayer Compliance, Taxpayer Awareness, Service Quality, Tax Sanctions